2021
DOI: 10.1259/bjr.20201453
|View full text |Cite
|
Sign up to set email alerts
|

Imaging diagnosis of basal ganglia germ cell tumors: subtype features subtype imaging features of GCTs

Abstract: Objectives: To evaluate the subtype imaging features of basal ganglia germ cell tumors (GCTs). Methods: Clinical and imaging data of 33 basal ganglia GCTs were retrospectively analyzed, including 17 germinomas and 16 mixed germ cell tumors (MGCTs). Results: The cyst/mass ratio of germinomas (0.53 ± 0.32) was higher than that of MGCTs (0.28 ± 0.19, p = 0.030). CT density of the solid part of germinomas (41.47 ± 5.22 Hu) was significantly higher than that of MGCTs (33.64 ± 3.75 Hu, p < 0.001), while apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In a retrospective review of intracranial germinomas and mixed germ cell tumours, Li et al had found that the incidence of intratumoural haemorrhage was significantly more in mixed germ cell tumours than in germinomas (68.75% vs 11.76%). 30 Liang et al also reported presence of intratumoural haemorrhage only in mixed germ cell tumours. 31 However, Chen et al noted presence of intracranial haemorrhage in 7 cases of germinomas and in 10 cases of non-germinomatous germ cell tumours.…”
Section: Discussionmentioning
confidence: 94%
“…In a retrospective review of intracranial germinomas and mixed germ cell tumours, Li et al had found that the incidence of intratumoural haemorrhage was significantly more in mixed germ cell tumours than in germinomas (68.75% vs 11.76%). 30 Liang et al also reported presence of intratumoural haemorrhage only in mixed germ cell tumours. 31 However, Chen et al noted presence of intracranial haemorrhage in 7 cases of germinomas and in 10 cases of non-germinomatous germ cell tumours.…”
Section: Discussionmentioning
confidence: 94%
“…Germinomas in the basal ganglia region are relatively rare with a strong male predominance ( 25 ). The most common manifestation is slow progressive hemiplegia, with involuntary movement, cognitive decline, language disorder, and personality change ( 30 ).…”
Section: Characteristics Of Germinomas At Different Sitesmentioning
confidence: 99%
“…Mild or no space-occupying effect is often observed. Hypointensity on T2* GRE/SWI and Wallerian degeneration of corticospinal tract, which is defined as ipsilateral atrophy of the cerebral hemisphere or cerebral peduncle, have been emphasized as reliable signs of basal ganglia germinoma ( 11 , 30 , 31 ) ( Figure 7 ). Hypointensity on SWI is very important in identifying early stages of germinomas.…”
Section: Characteristics Of Germinomas At Different Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The MRI appearance of suprasellar GCT spans from a small homogeneous stalk or infundibular lesion with absence of the normal T1WI neurohypophyseal bright spot to a larger predominantly solid mass with avid contrast enhancement and signs of reduced free water content, namely iso- to hypointense T2 signal and restricted diffusion (also high density on CT) ( 12 , 135 ). The former presentation overlaps with that of LCH, although a GCT diagnosis may be favored in the presence of hypothalamus infiltration or unilateral basal ganglia involvement, atrophy and Wallerian degeneration ( 135 , 136 ). A recent study by Esfahani et al ( 137 ) reviewed clinical and radiographic features of 42 pediatric suprasellar GCTs and found notable morphologic differences between solitary GCT and bifocal GCT.…”
Section: Sellar and Suprasellar Tumorsmentioning
confidence: 99%